(untitled) (Jurnal Bawaslu Provinsi Kepulauan Riau, 2023)
The electoral legal framework must be able to protect the rights of voters so that electoral law enforcement and justice can run and function honestly and impartially so as to create dignified elections. Bawaslu is given more powers by the Election Law, in addition to having prevention and supervision duties, Bawaslu is also given adjudication authority to handle administrative election violations. The research method used is normative juridical which includes primary, secondary and tertiary resources, data collected through literature study and then analysed qualitatively. The results showed that Bawaslu has the authority to take legal action if the election is not carried out in accordance with existing laws and regulations. This legal action can be in the form of punishment, allowing sanctions to be imposed on those who violate the law as well as constructive and binding in nature for parties involved in election violations. Related to the settlement of administrative election violations, Bawaslu is guided by Perbawaslu in providing an adjudication mechanism. Keywords: Election; Legal Framework; Bawaslu; Adjudication